The New Testament Canon and the 39th Paschal Epistle of St. Athanasius of Alexandria - Traychev, Emil (Forum Theologicum Sardicense, 2025)
Emil Traychev, The New Testament Canon and the 39th Paschal Epistle of St. Athanasius of Alexandria. The author attempts to explain the motives of St. Athanasius in writing the Paschal Epistle that mentions the number of books in the New Testament. He describes different stages in the life of St. Athanasius and his theological arguments to provide a proper context for writing the aforementioned epistle.